Atmospheric oxidation of fluoroalcohols initiated by ˙OH radicals in the presence of water and mineral dusts: mechanism, kinetics, and risk assessment. Issue 23 (2nd June 2021) - Bai, Feng-Yang; Deng, Ming-Shuai; Chen, Mei-Yan; Kong, Lian; Ni, Shuang; Zhao, Zhen; Pan, Xiu-Mei
Abstract : Mechanisms and kinetic investigations of ˙OH-initiated atmospheric oxidation of fluoroalcohols and the subsequent transformation: effects of water and silica particles. Abstract : The transport and formation of fluorinated compounds are greatly significant due to their possible environmental risks. In this work, the ˙OH-mediated degradation of CF3 CF2 CF2 CH2 OH and CF3 CHFCF2 CH2 OH in the presence of O2 /NO/NO2 was studied by using density functional theory and the direct kinetic method. The formation mechanisms of perfluorocarboxylic/hydroperfluorocarboxylic acids (PFCAs/H-PFCAs), which were produced from the reactions of α-hydroxyperoxy radicals with NO/NO2 and the ensuing oxidation of α-hydroxyalkoxy radicals, were clarified and discussed. The roles of water and silica particles in the rate constants and ˙OH reaction mechanism with fluoroalcohols were investigated theoretically. The results showed that water and silica particles do not alter the reaction mechanism but obviously change the kinetic properties. Water could retard fluoroalcohol degradation by decreasing the rate constants by 3–5 orders of magnitude. However, the heterogeneous ˙OH-rate coefficients on the silica particle surfaces, including H4 SiO4, H6 Si2 O7, and H12 Si6 O18, are larger than that of the naked reaction by 1.20–24.50 times. This finding suggested that these heterogeneous reactions may be responsible for the atmospheric loss of fluoroalcohols and the burden of PFCAs. In addition, fluoroalcohols could be exothermically trapped by H12 Si6 O18, H6 Si2 O7, and H4 SiO4, in which the chemisorption on H12 Si6 O18 is stronger than that on H6 Si2 O7 or H4 SiO4 . The global warming potentials and radiative forcing of CF3 CF2 CF2 CH2 OH/CF3 CHFCF2 CH2 OH were calculated to assess their contributions to the greenhouse effect. The toxicities of individual species were also estimated via the ECOSAR program and experimental measurements. This work enhances the understanding of the environmental formation of PFCAs and the transformation of fluoroalcohols.